'The illusion or the truth?' – Back stage constructions of authenticity in an up-market restaurant. (November 2019) - Maegaard, Marie; Karrebæk, Martha Sif
Abstract: Building on recent sociolinguistic and anthropological theories on authenticity, in this paper we take a sociolinguistic perspective on the construction of authenticity in a Copenhagen-based Bornholmian restaurant. Focus is on the tensions between different understandings of authenticity in the creation of a new predinner drink. Data include interactions between owner and staff where ingredients, serving, and glass design are negotiated, all connected to the general aim of creating a recognizable Bornholmian product. Through detailed discourse analyses it is shown how the potentiality of authenticity is created backstage in a contemporary commercial enterprise, and how understandings of authenticity as inherent quality or performed are not necessarily mutually excluding, but rather co-existing in contemporary commercial cultural encounters. Highlights: Shows how authenticity in a commercial context is not only about performance but also materiality and quality. Shows in detail how a commercial product is being created for consumer demands and the producer's aims. Offers a rare glimpse into back stage interactions in a restaurant where the commercial enterprise is being negotiated.